Postnatal Growth Trajectories and Neurodevelopmental Outcomes Following Bevacizumab Treatment for Retinopathy of Prematurity - Zhang DL; Yoon HH; deRegnier RAO; Arzu J; Rahmani S (Clinical Ophthalmology, 2022)
David L Zhang,1 Hawke H Yoon,1,2 Raye-Ann O deRegnier,3 Jennifer Arzu,4 Safa Rahmani1,2 1Department of Ophthalmology, Northwestern University Feinberg School of Medicine, Chicago, IL, USA; 2Division of Ophthalmology, Ann & Robert H. Lurie Children’s Hospital of Chicago, Chicago, IL, USA; 3Division of Neonatology, Ann & Robert H. Lurie Children’s Hospital of Chicago, Chicago, IL, USA; 4Division of Preventive Medicine, Northwestern University Feinberg School of Medicine, Chicago, IL, USACorrespondence: Safa Rahmani, Division of Ophthalmology, Ann & Robert H. Lurie Children’s Hospital of Chicago, 225 E. Chicago Ave, Chicago, IL, 60611, USA, Tel +1 312 227-6180, Fax +1 312 227-9411, Email SRahmani@luriechildrens.orgPurpose: To investigate the postnatal growth and neurodevelopment of infants with retinopathy of prematurity (ROP) treated with intravitreal bevacizumab (IVB).Patients and Methods: This was a retrospective comparative study. A total of 262 infants were divided among three study groups: 22 treated with intravitreal bevacizumab, 55 treated with laser, and 185 with ROP that resolved without treatment. Infants with nonviable course or hydrocephalus, a source of non-physiologic weight gain, were excluded. Neurodevelopment was assessed with Bayley III scores at 17– 28 months if available and presence of hearing loss or cerebral palsy. Weekly weight, height, and head circumference from birth through 50 weeks postmenstrual age (PMA) were modeled to determine differences in growth trajectories following treatment.Results: Comparison of postnatal growth curves from the time of treatment to 50 weeks PMA showed no significant differences in growth trajectories between groups after adjusting for the corresponding growth parameters at birth. Comparison of Bayley scores in patients with available data (n = 120) showed no significant differences. There was an increased risk of cerebral palsy in the IVB group after logistic regression adjusting for baseline confounders, but this did not retain statistical significance after applying the false discovery rate correction for multiple testing.Conclusion: To our knowledge, this is the first large retrospective study to examine longitudinal growth in infants treated with IVB compared to controls. There were no significant differences in postnatal growth or neurodevelopmental outcomes between groups, which overall continue to support the safety of bevacizumab treatment for ROP.Keywords: pediatric retina, ROP, laser, bevacizumab, neurodevelopment, growth